Blessing or curse: Impacts of the Brazilian Pre-Salt oil exploration - Aline Souza Magalh\~aes; Edson Paulo Domingues (EconomiA, 2014)
The discoveries of oil and gas in the so-called “Pre-Salt layer” have triggered a lot of discussions about their economic effect. In this paper we discuss in detail a less discussed dimension: the impact of Pre-Salt layer in the structure of the Brazilian economy, especially the composition of the industry and exports. Similar consequences in the country of “Dutch disease” and “deindustrialization” due to revenues from oil exports are evaluated. The methodology used is a dynamic global general equilibrium model, with specific features for the treatment of the issues raised. – – As descobertas de reservas de petróleo e gás na chamada “camada de Pré-sal” tem desencadeado uma série de discuss\~oes acerca do seu efeito econômico. Neste trabalho abordamos detalhadamente uma dimens\~ao menos discutida: os impactos do Pré-Sal na estrutura da economia brasileira, especialmente da composiç\~ao da indústria e da pauta de exportaç\~oes. Consequências no país similares às da “doença holandesa” e “desindustrializaç\~ao”, em decorrência das receitas com as exportaç\~oes de Petróleo, s\~ao avaliadas. A metodologia utilizada é um modelo de equilíbrio geral computável global, com características específicas para o tratamento das quest\~oes levantadas.
Keywords: Q32; Q34; L6; C68; 330; Pre-Salt; Dutch disease; Industry; Computable general equilibrium model